Pengaruh Pengetahuan Perpajakan, Kondisi Keuangan, Dan Ajaran Tri-Nga Terhadap Kepatuhan Pembayaran Pajak Bumi Dan Bangunan (Studi Kasus Wajib Pajak Di Wilayah Kecamatan Mlati) - Nur Anita Chandra Putri; Aktian Difianti (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study is to find out whether taxpayer compliance in paying land and building taxes is influenced by their knowledge of taxation, financial conditions, and Tri-Nga teachings. The study was conducted in Mlati District, Sleman Regency with a sample of 103 taxpayer respondents. The sampling strategy used is simple random sampling. Primary data is collected by distributing questionnaires to taxpayers. Answers to the questionnaire used in this study were quantified through scores or numerical values. The findings show that knowledge of taxation has no effect on taxpayer compliance with land and building tax payments, while economic conditions have a positive effect on land and building tax payer compliance and Tri-Nga teachings have a positive effect on land and building tax payer compliance. Keywords: Tax Knowledge, Financial Condition, Tri-Nga Teachings, and Taxpayer Compliance